Can Zakat Contribute to Achieving Sustainable Development Goals? A Case Study on Java Island, Indonesia. - Muttaqin, Zainal; Nasir, Mohammad Dendi Abdul (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
ABSTRACT In this paper, zakat is intended to stimulate sustainable development goals. The aim of this research is to examine the impact of zakat on human development programs using the variables economic growth, poverty, human development index, Gini index and gender development index. This research uses panel data covering all provinces on the island of Java for the 2010-2020 period. The data analysis model uses the Panel Vector Error Correction Model (PVECM). This research found that there is a two-way causal relationship between economic growth and zakat, while poverty, the human development index and the Gini index do not have a one-way or two-way causal relationship with zakat. The gender development index variable only has a one-way causal relationship with zakat. The findings further state that in the short and long term, zakat has a negative and significant effect on economic growth. In the short and long term, zakat has no effect on poverty, the human development index and the Gini index. In the short term, zakat has no effect on the Gini index. On the other hand, in the long term, zakat has a positive and significant effect on the Gini index. These results provide challenges as well as opportunities for stakeholders to improve zakat management. Zakat in Indonesia can be used as a fiscal policy tool to realize sustainable development goals. Keywords: Welfare, Zakat, SDGs, PVECM   ABSTRAK Dalam tulisan ini, zakat dimaksudkan untuk merangsang tujuan pembangunan berkelanjutan. Tujuan dari penelitian ini adalah untuk menguji dampak zakat terhadap program pembangunan manusia dengan menggunakan variabel pertumbuhan ekonomi, kemiskinan, indeks pembangunan manusia, indeks gini dan indeks pembangunan gender. Penelitian ini menggunakan menggunakan data panel yang mencakup seluruh provinsi di pulau jawa periode 2010-2020. Model analisis data menggunakan Panel Vector Error Correction Model (PVECM). Penelitian ini menemukan bahwa ada hubungan sebab akibat dua arah antara pertumbuhan ekonomi dan zakat, sedangkan kemiskinan, indeks pembangunan manusia dan indeks gini tidak mempunyai hubungan sebab akibat baik satu arah maupun dua arah dengan zakat. Variabel indeks pembangunan gender hanya mempunyai hubungan sebab akibat satu arah dengan zakat. Temuan selanjutnya mengatakan bahwa dalam jangka pendek dan jangka panjang, zakat berpengaruh negatif dan signifikan terhadap pertumbuhan ekonomi. Dalam jangka pendek dan jangka panjang, zakat tidak berpengaruh terhadap kemiskinan, indeks pembangunan manusia dan indeks gini. Dalam jangka pendek, zakat tidak berpengaruh terhadap indeks gini. Sebaliknya dalam jangka panjang, zakat berpengaruh positif dan signifikan terhadap indeks gini. Hasil ini memberikan tantangan sekaligus peluang bagi pemangku kepentingan untuk meningkatkan pengelolaan zakat. Zakat di Indonesia dapat digunakan sebagai alat kebijakan fiskal untuk mewujudkan tujuan pembangunan berkelanjutan. Kata Kunci: Kesejahteraan, Zakat, SDGs, PVECM